Bibliometric Study on Consumer Protection Law in the Global Business Context - Judijanto, Loso (Eastasouth Institute, 2024)
This bibliometric study delves into the realm of consumer protection law within the global business context, offering a comprehensive analysis of its historical evolution, research themes, temporal trends, influential authors, and prospective research directions. Spanning from 1951 to 2024 and encompassing 980 papers with 6,312 citations, the study illuminates the intricate web of academic literature. It identifies clusters of research themes, showcasing the field's interdisciplinary nature, and sheds light on emerging topics such as data protection and Islamic law in consumer protection. Notable authors and collaborations are highlighted, providing insights for scholars and policymakers, and emphasizing the global perspective in addressing consumer rights challenges in today's interconnected world.